Pulmonary Infections With Mycobacterium avium-intracellulare in Women With Confirmed or Suspected Malignancy. Issue 2 (March 2015) - Cheema, Asima; Yacoub, Abraham; Beltrame, Anna; Pasikhova, Yanina; Fahmi, Kerolos; Isabel, Maria; Ricciuti, Jason; Alrabaa, Sally; Greene, John
<x xml:space="preserve">Abstract</x> Background In the last 2 decades, there has been an increased interest in infections caused by nontuberculous mycobacteria (NTM). Mycobacterium avium complex is the most common PNTM in the United States. Pulmonary disease caused by MAI is often chronic and occurs particularly in the elderly, in women frequently without underlying lung disease. Although NTM infections are reported in patients with malignancy, few studies investigated the epidemiological, clinical, and radiological characteristics of pulmonary MAI infection in women with cancer. Materials and Methods We retrospectively reviewed medical and microbiologic records and radiographic findings of all female patients seen at the Moffitt Cancer Center in Tampa, Florida, with positive lung specimen cultures for MAI from January 1987 to January 2011. Microbiologic records included the cultures of expectorated sputum samples, bronchial wash or lavage, and lung biopsies. Radiographic findings obtained by high-resolution computed tomography permitted a classification of the lung MAI disease in 3 forms: cavitary, nodular bronchiectatic, and nodular form. Results A total of 46 patients met the inclusion criteria during a 24-year period. The median age at the time of diagnoses was 68 years. There were some patients who had an underlying cancer, an underlying chronic lung disease, and a comorbid condition. Cough was the most common pulmonary symptom in most of our patients. The most common radiologic finding was consistent with a single nodule. A few of the female patients were definable as Lady Windermere syndrome. Symptomatic improvement was seen in most of the patients with either a monotherapy or a combination therapy. Conclusions Physicians need to be aware of the possibility of coexisting pulmonary MAI in elderly women with cancer, principally breast and lung cancer, or chronic lung disease, with a chronic cough and a new nodule on the lung computed tomography scan. Early suspicion can lead to appropriate diagnosis, prompt therapy, and reduction of mortality.